The Effect of Human Resources Development and Morale on Temporary Employee’s Work Productivity at Pamong Praja Police Unit and Fire Department in Kabupaten Kaur - Kadri Kadri; Neri Susanti; Nia Indriasari (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of human resource development and morale on the productivity of temporary employees at Pamong Praja Police Unit and Fire Department of Kaur. The sample in this study was 125 employees. Data were collected using a questionnaire. The analytical method used was multiple regression analysis, hypothesis testing t and hypothesis testing f. The results of the regression equation are Y = 7.828 + 0.386X1 + 0.445X2 + 4.596, meaning that human resource development and morale have a positive influence on the productivity of employees at Pamong Praja Police Unit and Fire Department of Kaur. The result of the determination test is 0.557 or (55.7%). This shows that human resource development and morale affect the productivity of employees at Pamong Praja Police Unit and Fire Department of Kaur by 55.7%, while the rest (100 - 55.7% = 44.3%) is explained or influenced by other variables not examined. Human resource development and morale together have an influence on the productivity of the temporary workers at Pamong Praja Police Unit and Fire Department of Kaur with a significant value of 0.000, less than 0.05. Human resource development has a positive and significant effect on the productivity of temporary employees at Pamong Praja Police Unit and Fire Department of Kaur, because the significant value of 0.003 is smaller than 0.05. Morale has a positive and significant effect on the productivity of on the productivity of temporary employees at Pamong Praja Police Unit and Fire Department of Kaur, with a significant value of 0.000, which is smaller than 0.05